Functional Features of the Digestive System in Retired Athletes - Fedorovich Panov, Sergey; Petrovna Panova, Irina (International Journal of Psychosocial Rehabilitation, 2020)
According to many researchers, the abrupt cessation of motor activity in athletes can be considered as a stress factor for the body, which accordingly leads to disorganization and disruption of all functional systems. The paper presents the results of a study on functioning of the retired wrestlers’ digestive system and discusses the findings concerning the digestive conveyor functioning in a state of muscle rest in former wrestlers as compared to their peers who are not engaged in sports activities. Our research materials show that the retired athletes’ digestive system functioning is characterized by severe inhibition of gastric acid juice secretion in basal secretion, as well as acid-forming and enzyme excretory functions in basal and stimulated digestive tract secretion. These factors result in a decrease in proteolysis. The peak drop in reactivity and the level of total proteolytic activity in former athletes is most likely caused by a decrease in the level of physical activities. It was revealed that the stage of finishing with a sports career or as we call it “post-sport ontogeny” can be referred to as a critical period of the former athlete’s life from the standpoint of the digestive system functioning, which manifests itself in the inhibition of the main indicators of the gastric glands. Undoubtedly, the presented results of this series of studies require further research, since the period of the subsequent lifestyle of former athletes is quite long.